PENGARUH EKSTRAKSI DAN JENIS BAHAN PENGIKAT TERHADAP PERMEN TABLET BUAH MENGKUDU (Morinda citrifolia) - Lina Widawati (BPFP Faperta UNIB, 2011)
Noni (Morinda Citrifolia) is a herb which has effect to cure cancer, high blood pressure, etc. Makes the smell and the taste of noni less delicious because there are a number of organic acid like caproic acid and caprilic acid in noni. Therefore it needs an alternative product such as pressed candy. Correct process of extraction and addition of binding agents can produce the pressed candy with the physical, chemical and organoleptic characteristic that are expected. The objective of this research wash to know the optimum ratio of noni compared with ethanol so it can produce dry extrac of noni fruit with vitamin C and high activity antioxidant and also to know the influence of binding agents type in the making of noni pressed candy. This research use the Randomized Block Design (RBD), where at antecedent research consisted of 3 (three) levels which is ratio of noni fruit compared by ethanol (1:1, 1:2, 1:3) and best treatment used for the main research. Main research consisted of 3 (three) levels that was influence of binding agents type (maltodextrin 5%, gelatin 1,5% and gom arab 1%). Then its continued with the BNT test at ? = 0,05 (differing reality). Test of organoleptic done by hedonic score test. Best treatment uses multiple attribute method. The result of research show that the best treatment from dry filtrate of noni fruit was with the ratio of noni fruit compared by ethanol = 1:3. Best treatment of noni fruit pressed candy is with the gelatin addition 1,5 %.